Avaliação de desempenho de respostas motoras combinadas à digitação em diferentes teclados utilizados em dispositivos móveis - Alleoni, Bruno Nascimento [UNESP] (2013)
The use of mobile phones and tablets is becoming more common in our society, be it for communication, games or reading. Communication may be by voice or text message and different situations as in a classroom or even in traffic. This study was based on the behavior of imminent risk of accident, increasingly, people using the mobile phone in transit to exchange text messages. Two experiments with the following objectives were achieved: analyzing the performance of older adults and typing text copied and stored in two types of keyboards, progress conventional and virtual text displayed on the capacitive touchscreen of a type of cell phone, and; analyze interference with the task of typing a text stored on a task of visual reaction time to press a brake pedal with the right foot. This study shows that text entry by adults and elderly was faster when taken with the conventional progress keyboard. The participants found it is easier and less tiring to use the conventional progress keyboard than using the touchscreen. Adults can divide more attention than seniors, but venture further to the risk and may be more susceptible to involvement in a traffic accident. The use of the mobile device for entering text leads to a considerable increase in response time to a visual stimulus, being highly indicated that traffic laws are updated in relation to the use of telecommunication devices. And that the operating system of any motor vehicles keep their conventional drive keys due to the potential injury to use attention on a virtual button could cause